LATE QUATERNARY CATASTROPHIC FLOODING IN THE ALTAI MOUNTAINS OF SOUTH-CENTRAL SIBERIA: A SYNOPTIC OVERVIEW AND AN INTRODUCTION TO FLOOD DEPOSIT SEDIMENTOLOGY - Carling P.A.; Kirkbride A.D.; Parnachov S.; Borodavko P.S.; Berger G.W. (My University, 2002)
This paper provides an overview of the geography and palaeogeography of the Chuja (Chuya)–Katun river system in the Altai Mountains of south Siberia. In addition, an introduction to the sedimentology of catastrophic flood deposits is provided. Tracts of large gravel dunes and giant gravel bars in the Katun and Chuja river valleys of south-central Siberia are testimony to episodes of catastrophic flooding that occurred owing to the sudden emptying of the ice-impounded glacial lake Kuray–Chuja primarily during the Late Pleistocene (40 ka to 13 ka). Although today there are no substantial water bodies in the Kuray and Chuja basins, glaciolacustrine deposits attest to the former presence of large ice-proximal lakes, whereas multiple strandlines at various elevations around the basin margins indicate former lake levels. Floods were of a scale similar to that recorded for glacial-lake Missoula in North America. A large flood down the main Chuja and Katun river valleys deposited huge quantities of coarse and fine gravels within back-flooded tributary mouths and other valley-side embayments. Today these deposits form giant bars that blanket the valley walls and block each tributary entrance for a distance of over 70 km. While the bars were being deposited, the base of the main valley was infilled to a depth of 60–90 m by coarse-gravel traction deposits. In particular coarse gravel bedload and hyperconcentrated-flow units prograded down-valley beneath flood waters several hundred metres deep. Locally, steeply cross-stratified units, each several decimetres thick attest to steep bar-front progradation similar in style to a Gilbert-type delta.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная